2010
DOI: 10.1016/j.biomaterials.2010.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete fiber network topology of planar fibrous tissues and scaffolds

Abstract: Understanding how engineered tissue scaffold architecture affects cell morphology, metabolism, phenotypic expression, as well as predicting material mechanical behavior have recently received increased attention. In the present study, an image-based analysis approach that provides an automated tool to characterize engineered tissue fiber network topology is presented. Microarchitectural features that fully defined fiber network topology were detected and quantified, which include fiber orientation, connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
164
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 144 publications
(167 citation statements)
references
References 55 publications
3
164
0
Order By: Relevance
“…On the other hand, fiber extraction algorithms have only recently been implemented for quantifying structural characteristics of fibrous networks [49,[61][62][63][64]. In this study the two techniques were combined to yield complementary quantitative data, and at the same time this This quantitative structural analysis has shown that changes in fibrinogen, thrombin, factor XIII and calcium concentrations induce significant changes in the structure of the hydrogels, both in terms of the overall network organization and individual fiber characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fiber extraction algorithms have only recently been implemented for quantifying structural characteristics of fibrous networks [49,[61][62][63][64]. In this study the two techniques were combined to yield complementary quantitative data, and at the same time this This quantitative structural analysis has shown that changes in fibrinogen, thrombin, factor XIII and calcium concentrations induce significant changes in the structure of the hydrogels, both in terms of the overall network organization and individual fiber characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many efforts have been devoted to study the mechanical behavior of a single collagen fiber (Annovazzi and Genna 2010;Ogden 2011, 2013). Also, more detailed geometric information regarding the fiber microscopic arrangement can be acquired via advanced image processing technologies such as confocal reflection imaging (Roeder et al 2002;Arganda-Carreras et al 2010) or scanning electron microscopy (SEM) (D'Amore et al 2010). All these advances make it possible to obtain the material parameters completely from experiments.…”
Section: Discussionmentioning
confidence: 99%
“…First, the microstructure of many samples is highly complex [5]. For example, there are hundreds of substructures with different shapes and sizes (e.g., "dendritic structure" in Al-La alloy [6], "grains" in polycrystalline iron [2], or "cells" in biomaterials [7], etc.) which must be accurately segmented in each image.…”
Section: Introductionmentioning
confidence: 99%